PENGARUH PEMBELAJARAN DARING TERHADAP MINAT BELAJAR SISWA MAN 4 PEKANBARU - Sri Wahyuni Harahap; Supentri Supentri; Indra Primahardani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by online learning on student interest in MAN 4 Pekanbaru, this online learning certainly has an impact on student interest in MAN 4 Pekanbaru. The formulation of the problem in this study is whether there is an effect of online learning on student interest in MAN 4 Pekanbaru. This study aims to determine whether there is an effect of online learning on student interest in MAN 4 Pekanbaru. The population in this study were all students of MAN 4 Pekanbaru, totaling 274 students consisting of 10 classes, 20% of the population will be taken from the population so that 55 students are the sample in this study, taking 20% of the population because it is impossible for the entire population to be sampled. In this study, the sampling was determined by proportional random sampling technique. This sampling technique was used to avoid injustice. The instruments used in this study were questionnaires, and interviews, in processing data the researchers used quantitative research where the data obtained would be processed with the help of SPSS version 16. 95% confidence level and 5% significant so that Ho is rejected and Ha is accepted, which means online learning has an effect on student interest in MAN 4 Pekanbaru. The coefficient of determination (R Square) is 0.518, which means the effect of online learning on interest in learning is 51.8% so that there is a significant influence between learning on student interest in MAN 4 Pekanbaru, while the remaining 48.2% (100%-51.8% ) is influenced by other variables not examined in this study or influenced by other factors outside the X variable.Key Words : Influence, Online Learning, Student Interests.